Analysis of Inherent Risk Management in the Digital Delivery of General Insurance Products Within the Iso 31000:2018 Framework at HGI Insurance - Imelda Stella M. (International Journal Labs, 2026)
The integration of information technology has fundamentally transformed the insurance industry, particularly in the digital delivery of general insurance products. This study examines the implementation of ISO 31000:2018, a risk management framework, in managing inherent risks at HGI Insurance during its digital transformation. The primary objective of this research was to evaluate the application of ISO 31000:2018 in the management of digital insurance product risks, focusing on inherent risks such as operational, compliance, legal, and reputational risks. Using a qualitative descriptive approach with evaluative-prospective orientation, this study analyzes primary data from interviews with key informants at HGI Insurance and secondary data from internal and external documents. The findings reveal that while the risk management system aligns with ISO 31000:2018 principles, it is still in the early stages of full integration. The company's risk management policies and frameworks have been adapted to digital operations, and there is an ongoing effort to improve cross-functional coordination and develop a fully integrated risk management system. The study concludes that although the digital transformation presents new challenges, HGI Insurance is making significant strides in enhancing its risk management capabilities, ensuring compliance with both ISO 31000:2018 and the Financial Services Authority's regulations .